A new approach to geo-visualizing public security data: the case of study of the public prosecutor of Rio Grande do Norte state, Brazil (Revista Espinhaço, 2019)
In this research, we address problems associated with information without spatial context in public security, specifically in the Public Ministry of Rio Grande do Norte (PMRN). We have shown that information without spatial context makes the investigative analysis more difficult, increasing investigation time and weakening strategies. To address this problem, we investigate the use of geo-technology in the context of public management, with emphasis on public security management. We have identified in the literature the significant use of geo-technologies in processing public security data in criminal areas, but not in civil and administrative areas. We have explored this gap, structuring and developing a geo-visualizer of the occurrences recorded in the PMRN. Structured from interviews with prosecutors, and developed through Google Maps API, the geo-visualizer contributes to: i) to correlate (visually) investigations by proximity; ii) reduce the time in the displacements in the work areas; and (iii) increase the institution’s investigative capacity.
Keywords: public security; spatial data processing; geo-technologies; geo-visualizer; Public Ministry